Response of the natural grassland vegetation change to meteorological drought in Xinjiang from 1982 to 2015 - Zhao, Weikang; Jing, Changqing (Frontiers in Environmental Science, 2022)
In recent years,the frequency of drought has gradually increased,which has restricted the growth and development of vegetation.The response of grassland to meteorological drought is more sensitive,and the response of different grassland types to meteorological drought is quite different.Based on the data of normalized vegetation index (NDVI) and the standardized precipitation evapotranspiration index (SPEI) ,this study analyzed the spatial and temporal variation trends and correlations of NDVI and SPEI of different grassland types in Xinjiang from 1982 to 2015,so as to evaluate the response of vegetation change to meteorological drought at different time scales.The results showed that:1)In the past 34 years, the NDVI of meadow, steppe and desert grassland in Xinjiang showed an insignificant increasing trend (p>0.05),and the growth rates per decade were 0.002,0.002 and 0.0003,respectively.The most obvious vegetation improvement areas of the three grassland types are mainly distributed in the Tianshan Mountains.2)The SPEI-12 of meadow,steppe and desert grassland in Xinjiang showed an extremely significant drying trend (p<0.01),and the change rates per decade were -0.31,-0.38 and -0.34,respectively.The overall performance was gradually drying from northwest to southeast,and the degree of aridification in eastern Xinjiang was the most obvious.3) On the annual scale,the correlation between NDVI and SPEI-12 of the three grassland types was significantly different in the northern and southern Xinjiang.Compared with the southern Xinjiang,the response degree of vegetation of the three grassland types to drought in northern Xinjiang was higher and most of them were significant.On the monthly scale,the response of meadow to SPEI-12 was the highest in autumn (September)(r=0.53,p<0.05),the response of steppe to SPEI-3 was the highest in summer (August)(r=0.49,p<0.05),and the response of desert grassland to SPEI-12 was the highest in summer (June)(r=0.44,p<0.05).The results can provide scientific basis for natural grassland drought response,ecological environment improvement and disaster prevention and mitigation.